DIGITAL TRANSFORMATION AND TAX AVOIDANCE OF THE INDONESIAN BASIC MATERIALS AND ENERGY SECTOR - Nanda Lestari, Dwi Novita; Kholid, Muamar Nur (Faculty of Economics and Business University of Mataram, 2024)
This study was conducted to obtain empirical evidence regarding the effect of profitability, digital transformation, CFO co-optation, fixed asset intensity, institutional ownership, and independent commissioners on tax avoidance in companies included in the basic material sector category listed on the Indonesia Stock Exchange in 2018-2021. The sampling technique in this study used the purposive sampling method so that as many as 30 companies were obtained. The data analysis method uses multiple regression analysis. The results of this study show that CFO co-optation and intensity of fixed assets positively affect tax avoidance. Meanwhile, digital transformation does not affect tax avoidance. Furthermore, this study discusses research results in theoretical and practical domains.